Social Solidarity in Manyaratuih Hari (The 100th Day) Tradition in Taluak Community Tanah Datar Regency West Sumatra - Siska Elasta Putri (Alfuad: Jurnal Sosial Keagamaan, 2024)
The background of this research was the interest in seeing Taluak communityÔÇÖs social solidarity in carrying out manyaratuih hari tradition. Manyaratuih hari (the 100th day) is a tradition held on the 100th day of the death of a family member on which the family serves meals to the invited community members. Carrying out manyaratuih hari is an obligation because this traditional belief is a custom in Taluak community. Based on the observation, this research revealed the face of the communityÔÇÖs social solidarity in this tradition. A qualitative research method with ethnography was used in conducting this research. The result showed that the communityÔÇÖs social solidarity in carrying out manyaratuih hari was performed in the stages of (1) Preparing manyaratuih hari such as providing money, mamanggia (invitation), making temporary kitchen (bauang-bauang), building a tent, finding bamboo reeds, bamboo shoots, fire woods, and cooking some food, (2) Holding manyaratuih hari: serving the food, giving bawokan (by the guests), welcoming and taking bawokan from the guests.